The Size of Venture Capital and Private Equity Fund Portfolios - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2007)
We propose a model that examines the optimal size of venture capital and private equity fund portfolios. The relationship between a VC and entrepreneurs is characterized by double-sided moral hazard, which causes the VC to trade off larger portfolios against lower values of portfolio companies. We analyze the structural relations between the VC's optimal portfolio structure and entrepreneurs' and VC's productivities, their disutilities of effort, the value of a successful project, and the required initial investment in a venture. We also test the model's predictions using a small proprietary dataset collected through a survey targeted to VC and private equity funds worldwide.